Komunikasi Pemasaran Digital bagi UMKM Desa Tridaya Sakti sebagai wujud literasi digital UMKM di Kabupaten Bekasi - Dewi Rachmawati; Riska Afrianti; Stephanny Lianardo (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Abstract Digital Marketing Communication for MSMEs in Tridaya Sakti Village as a form of digital literacy for MSMEs in Bekasi Regency Dewi Rachmawati (dewi.r@lspr.edu) Riska Afrianti (riska.a@lspr.edu) Stephanny Lianardo (stephanny.l@lspr.edu) Faculty of Communication – LSPR Communication & Business Institute The digital literacy movement is currently being intensified by the government to all levels of society. With this movement, it is hoped that people will not only be technology literate and be able to use it, but also understand and have digital skills and be responsible for using it. One of the scopes that become the target of digital literacy is MSMEs (Micro, Small and Medium Enterprises) especially in villages. In terms of marketing communications, this digitalization is carried out so that MSMEs can increase their level and can reach wider marketing in a faster, more effective and efficient. The LSPR Institute of Communication and Business, has played a role in accelerating digital literacy for MSMEs by holding workshops through online media for MSMEs in Tridaya Sakti Village, Tambun Selatan District, Bekasi Regency. Total of 11 MSMEs from Tridaya sakti Village attended the online workhop with the title Business Marketing Communication and Services Through Social Media in Business Groups in Tridaya Sakti Village. MSME participants realize the important role of marketing communication through social media, which currently can reach distant customers quickly. However, in its application there are still some obstacles experienced such as lack of skills in using technology and understanding of social media content itself, product photos and internet connections. Participants are also encouraged and will use social media to support their business marketing communications. Keywords : digital marketing communication; digital literacy; MSMEs